PEMODELAN KEDEPAN GEOLISTRIK RESISTIVITAS MENGGUNAKAN METODE BEDA HINGGA (KASUS 2D: MODEL LAPISAN YANG HOMOGEN) - Fitria Dwi Andriani; Elza Anisa Suwandi; Hafshah Suria Dhani; Firmansyah Firmansyah; Selly Feranie (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
In exploration geophysics, modeling is a way to interpreting the distribution of the earth response of a subsurface geological conditions specific. Resistivity geoelectric forward modeling for 2D case has been done by applying the finite difference method using Matlab software to solve a differential equations system, in this case it is Poisson equation. The solution of differential equations is done by discretization it using central finite difference approximated by taylor series expansion resulting a linear equations , where A is a sparse matrix, x is the electric potential at each grid, and B is the electric current matrix vector. Layer model used in this study is a 20x20 grid homogeneous layer. Calculation results show that the model response (resistivity value) on the surface is dependent on the boundary conditions and sensitive to electrode spacing changes (in this case using the Configuration Wenner). This program is able to provide results approaching the initial model values when surface measurements do not approach both the edge of the grid model side and electrode spacing in the range of 1 to 3 pixels (grid). Keywords: finite difference method, homogen modelling, resistivity forward modelling 2D.